Heavy Metal Levels in Tissues of Cyprinus carpio from Kaz Lake in Tokat, Turkey - KARATAS, MEHMET; SEKER, YASAR (Asian Journal of Chemistry, 2010)
In this research, samples of commonly consumed fish (Cyprinus carpio) were analyzed for concentrations of heavy metals (Al, Cd, Mn Cr, Cu, Fe, Ni, Pb, V and Zn) inhabiting the Kaz Lake (Tokat, Turkey). Heavy metal contents of muscle, gill and gonad tissues was detected in fresh matter by atomic absorption spectrophotometer and counted in mg kg-1. With respect to concentrations of pollutants in the Kaz Lake should not pose any threat to the fishes and public health.